Histological identification of H. pylori stained by hematoxylin-eosin and Giemsa: review for quality control - Marcela S. Boldt; Rivelle D. Pereira; Alfredo J. A. Barbosa (Sociedade Brasileira de Patologia Clínica, 2015)
Introduction: Several special staining methods are available for H. pylori (Hp) identification in histological sections of chronic gastritis (CG), including the routine hematoxylin-eosin (HE) method. Some reports suggest that ancillary stains are not always needed to establish the diagnosis of Hp infection. In addition, the benefit of using them, when biopsies show minimal inflammation, is not clear. Objective: We performed a retrospective study to compare the usefulness of HE with Giemsa method for the histopathological diagnosis of Hp in tissue sections. Methods: Histological sections from 390 consecutive patients were reviewed. The patients were registered in the histopathology laboratory of Instituto Alfa de Gastroenterologia, Hospital das Clínicas da Universidade Federal de Minas Gerais (UFMG), Belo Horizonte, Brasil. They were divided in 4 groups according to the gastric inflammatory changes as follows: Group I, gastric mucosa with normal morphology or minimal inflammatory changes (n = 146); Group II, chronic gastritis (CG) with mild inflammatory activity (n = 101); Group III, CG with patent inflammatory activity (n = 123); Group IV, patients with atrophic body gastritis (n = 20). All histological sections were carefully evaluated by 2 examiners at the oil immersion objective (1000×). Results: The identification of Hp was positive by Giemsa and HE, respectively at: Group III, 111 (90.2%) and 93 (75.6%) patients (p < 0.01); Group II, 43 (42.6%) and 29 (28.7%) patients (p < 0.05). Hp was negative in Groups I and IV. Conclusion: The results show that Giemsa stain is superior to HE for histological identification of Hp in CG. Although Hp could be identified by HE stain in the majority of CG cases, a significant number of infected patients may be neglected, regardless the intensity of the inflammatory response.